Adoption of Innovative Livestock Technologies: Potentials and Constraints among the Smallholder Farmers - Md Abdul, Quddus (INTI International University, 2024)
The study was undertaken to know the features of implementation and identify the conveniences and limitations of innovative livestock technologies to facilitate the researchers and farmers for refining the adoption level as well as to enhance the animal and poultry productivity. The north-central part of Bangladesh was chosen and 4 different agro-ecological zones were selected for the study. Categorical data were gathered from the selected farmers through oral interviews and they were presented graphically.Technologies were developed mostly for research and industrial uses by the researchers but they were not adopted sufficiently by the farmers. Farmers adopted the technologies mainly to get more production and income generation. Farmers had easy access to improved breeds and vaccines and moderate access to off-farm activities and transport facilities. Lack of availability of disease control technologies and absence of proper demonstration were the common and frequent constraints for the smallholder adopters. Also, inadequate information for access to technologies, lack of technical knowledge and absence of reliable technical assistance were the remarkable problems in adoption. It is recommended that farmers should have easy access to extension offices, providing input subsidies and special financial interventions for the higher rate of adoption of innovations by the smallholders.